Primary stability in hip revision arthroplasty: comparison of the stability of cementless fixed augments on a modular acetabular cage system with and without cranial straps - Jaenisch, Max; Kohlhof, Hendrik; Wirtz, Dieter Christian; Schildberg, Frank Alexander; Beckmann, Nicholas A.; Kretzer, Jan Philippe; Schonhoff, Mareike; Jäger, Sebastian (Journal of Clinical Medicine, 2021)
The goal of this study is to evaluate the primary stability of a cementless augment-and-modular-cage system with and without the addition of cranial straps in a standardized in vitro setting. As the surrogate parameter for the evaluation of primary stability, the measurement of relative motion between the implant components themselves and the bone will be used. Acetabular revision components with a trabecular titanium augment in combination with a large fourth-generation composite left hemipelvis were assembled. These constructs were divided into two groups with (S) and without cranial straps (nS). A total of 1000 cycles was applied at each of three load levels. Relative movements (RM) between the components were measured. Load levels display a significant effect on the amount of RM at all interfaces except between shell/augment. The group assignment appears to have an effect on RM due to significantly differing means at all interfaces. Between bone/shell RM increased as load increased. NS displayed significantly more RM than S. Between shell/augment RM remained constant as load increased. Between shell/cup S showed more RM than nS while both groups’ RM increased with load. We conclude a significant increase of primary stability between the shell and the bone through the addition of cranial straps. Relative motion between components (shell/cup) increases through the addition of cranial straps. A clinical impact of this finding is uncertain and requires further investigation. Finally, the cementless fixation of the augment against the rim-portion of the shell appears stable and compares favorably to prior investigation of different fixation techniques.
Gesehen am 18.10.2021